Measuring Educational Outcomes in Higher Education – General and Specific Competencies for Psychosocial Work - Huić, Aleksandra; Ricijaš, Neven; Branica, Vanja (2007)
Recently, facilitated by the widespread reform of European higher education, we are witnessing a shift towards competency-based approaches to research of educational outcomes. New curricula clearly state the competencies students should develop as a result of a learning program. Authors are becoming increasingly interested in different methodologies when it comes to competency assessment. The purpose of this study was to implement a self-report approach to the measurement of educational outcomes. Our goal was to find out how students themselves perceive the importance of general competencies for their future work in the psychosocial domain, and whether they feel they are able to perform specific work tasks required for successful job performance. The study was a collaborative effort between different “ helping” professions. The goal was to compare social work, social pedagogy and psychology students. Although they undergo different curricula, they can all find a job within the domain of psychosocial work. The study was conducted at the University of Zagreb, Croatia. A total of 138 senior year students participated in the study. 54 psychology students, 43 social work students and 41 social pedagogy students were involved. Most of them were females (97%). Data on students' satisfaction with general knowledge and skills gained through their education, student practice, volunteer work and professional interest in psychosocial work were gathered. Students were also asked to assess the level of certain general competencies acquired through education together with the importance of these for their future work. ‘ Perceived Competency for Future Psychosocial Work Scale’ was also administered. This Scale was developed in the preliminary research that preceded this study. Participants assessed how sure they are that they can successfully perform specific activities in the domain of psychosocial work (common to all three investigated professions). Differences between three university groups considering students' satisfaction with the knowledge and skills gained, and their perception of competency for their future work within the psychosocial domain are discussed. A disparity between the competencies thought to be important by educators and the competencies students perceive are important can indicate a gap in the learning process. Results on the general competencies scale are viewed in the context of the outcomes stated in the curriculum. Differences between the professions are discussed in the context of the differences between their curricula. Future considerations and the utility of this methodological approach for the assessment of educational outcomes are elaborated.
Projekt MZOS
Projekt MZOS
ENG